VD_FINDINFO HC / 2013 / 610 vom 1. Oktober 2013 - VD Tribunal cantonal (2013)
EXPULSION DE LOCATAIRE, PAIEMENT DE L'ARRIÉRÉ, IMPUTATION, RESTITUTION DU DÉLAI | 257d CO, 86 CO, 87 CO, 148 CPC (CH), 257 CPC (CH)